2015
DOI: 10.1002/nla.1972
|View full text |Cite
|
Sign up to set email alerts
|

Fast approximate inversion of a block triangular Toeplitz matrix with applications to fractional sub‐diffusion equations

Abstract: SummaryA fast approximate inversion method is proposed for the block lower triangular Toeplitz with tri‐diagonal blocks (BL3TB) matrix. The BL3TB matrix is approximated by a block ϵ‐circulant matrix, which can be efficiently inverted using the fast Fourier transforms. The error estimation is given to show the high accuracy of the approximation. In applications, the proposed method is employed to solve the fractional sub‐diffusion equation whose discretized matrix by a finite difference method is a BL3TB matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…Note that if the numerical solutions in all time steps are stacked in one vector, then the finite-difference discretization of Equation 1 can lead to the following block lower triangular Toeplitz (BLTT) system 16,17 :…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that if the numerical solutions in all time steps are stacked in one vector, then the finite-difference discretization of Equation 1 can lead to the following block lower triangular Toeplitz (BLTT) system 16,17 :…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, another type of method, named the approximate inversion method (AIM), has been proposed by Lu et al 17 to fast solve the BLTT system (2). Based on the BLTT structure, the authors approximated the coefficient matrix of Equation 2 by the block -circulant matrix, which can be block-diagonalized by the Fourier matrix and diagonal matrix in (mn log n) operations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical results have shown that compared with Robust Principal Component Analysis (RPCA)‐based models, the proposed methods are much efficient and effective. In the fifth paper, Lu et al developed a fast approximate inversion method for solving block lower triangular Toeplitz with tridiagonal blocks systems. In applications, the proposed method is employed to solve the fractional subdiffusion equation very efficiently.…”
mentioning
confidence: 99%